2013
DOI: 10.1371/journal.pone.0066257
|View full text |Cite
|
Sign up to set email alerts
|

Tannins Possessing Bacteriostatic Effect Impair Pseudomonas aeruginosa Adhesion and Biofilm Formation

Abstract: Plants produce many compounds that are biologically active, either as part of their normal program of growth and development or in response to pathogen attack or stress. Traditionally, Anadenanthera colubrina, Commiphora leptophloeos and Myracrodruon urundeuva have been used by communities in the Brazilian Caatinga to treat several infectious diseases. The ability to impair bacterial adhesion represents an ideal strategy to combat bacterial pathogenesis, because of its importance in the early stages of the inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
82
0
11

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(101 citation statements)
references
References 33 publications
8
82
0
11
Order By: Relevance
“…24,25 Additionally, TA inhibits S. aureus, P. aeruginosa and E. coli biofilm formation in multiple biofilm models. [26][27][28] Bacterial infection is one of the most serious complications impairing wound healing and tissue regeneration, which may lead to prolonged inflammatory responses, and hence it delays wound recovery. Here, we showed that AgNPs modified with TA inhibited bacterial growth more effectively than TA-modified or unmodified AgNPs (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…24,25 Additionally, TA inhibits S. aureus, P. aeruginosa and E. coli biofilm formation in multiple biofilm models. [26][27][28] Bacterial infection is one of the most serious complications impairing wound healing and tissue regeneration, which may lead to prolonged inflammatory responses, and hence it delays wound recovery. Here, we showed that AgNPs modified with TA inhibited bacterial growth more effectively than TA-modified or unmodified AgNPs (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…The antimicrobial and antibiofilm activity of various aerial parts of Moringa oleifera was in order: mLe > mBa >mFl>mFr>mSt and these activities were due to the presence of phytochemical compounds like saponins,aterpenoids, alkaloids, carbohydrates, fats, tannins, flavonoids and sterols. The various phytochemicals and secondary metabolites have been reported to exhibited antimicrobial activities (Trentin et al, 2013;Manner et al 2013). The leaf and bark showed highest zone of inhibition at the concentration of 100 µg/disc and as an antibiofilm against bacterial pathogens while at same concentration of 100 µg/dics the other extracts showed least antibacterial and antibiofilm activity against the studied bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…This plant has been subject of several studies about its pharmaceutical potential. [4][5][6][7]12,17 In our previous studies the antimicrobial action of extracts and fractions from leaves and fruits of A. colubrina was reported against Gram-positive bacteria, and no activity was observed against Gram negative bacteria. [4][5][6]12 In the present work we employed a different extraction method, by which we obtained extracts with activity against tested Gram negative bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 For some of those, scientific evidences confirm these therapeutic aptitudes. [4][5][6][7] In recent years, the ethnomedicinal knowledge has stimulated several studies about the pharmaceutical potential of natural products of northeastern Brazil. 8 This is justified by the fact that the intrinsic features of Caatinga area (drought, high solar radiation rates and other environmental stresses) influence the synthesis of secondary metabolites of its plants, 9 making them attractive targets for bioprospecting programs.…”
Section: Introductionmentioning
confidence: 99%